Role of CXCR4 and SDF1 as prognostic factors for survival and the association with clinicopathology in colorectal cancer: A systematic meta-analysis - Yao-ping Li; Jing Pang; Sheng Gao; Peng-yu Bai; Wen-da Wang; Pengzhou Kong; Yongping Cui (Tumor Biology)
C-X-C chemokine receptor type 4 and stromal cell–derived factor-1 were proven to play important roles in several types of cancer and in many biological processes connected with tumor growth, invasion, angiogenesis, and metastasis. However, the clinical significance of C-X-C chemokine receptor type 4 and stromal cell–derived factor-1 expression in colorectal cancer remains inaccurate. The purpose of this systematic meta-analysis is to investigate the role of C-X-C chemokine receptor type 4 and stromal cell–derived factor-1 as prognostic factors for survival and the association between C-X-C chemokine receptor type 4/ stromal cell–derived factor-1 and clinicopathology in colorectal cancer. Databases including PubMed, EMBASE, and Cochrane Library were searched for relevant literatures updated till January 2017. Review Manager 5.3 was used for data analysis. In our meta-analysis, C-X-C chemokine receptor type 4 expression is related to tumor–node–metastasis stage, tumor differentiation, liver metastasis, lymph node metastasis, distant metastasis, and diagnosis, and no correlation of C-X-C chemokine receptor type 4 expression with tumor size, gender, preoperative carcinoembryonic antigen, age, or vascular invasion has been observed. Stromal cell–derived factor-1 expression has no relationship with tumor–node–metastasis stage, lymph node metastasis, vascular invasion, age, gender, distant metastasis, or diagnosis. The expression of stromal cell–derived factor-1 has association with tumor differentiation. Moreover, the pooled hazard ratio for disease-free survival/overall survival showed that overexpression of C-X-C chemokine receptor type 4/stromal cell–derived factor-1 reduced disease-free survival/overall survival in colorectal cancer. Therefore, High expression of C-X-C chemokine receptor type 4/stromal cell–derived factor-1 which is essential in tumor progression can predict poor survival that may provide more advance prognostic clues to colorectal cancer patients.